Strategi Membangun Brand Awareness Melalui Media Sosial Instagram: Studi Kasus PTM Gunung Salak Denpasar - Nyoman Alit Septiningsih; Kadek Adyatna Wedananta (Badan Penerbit STIEPARI Press, 2026)
This study explores the strategic use of Instagram as a promotional medium to build brand awareness at PTM Gunung Salak Denpasar. As a Micro, Small, and Medium Enterprise (MSME), PTM Gunung Salak utilizes digital media to expand promotional reach and enhance brand image. The research employs a descriptive qualitative method with data collected through observation, interviews, and documentation. Informants include the business owner, employees, and court renters selected through purposive sampling. The results indicate that Instagram serves effectively as a visual promotional tool and a two-way communication platform between the business and consumers. Through visual content such as photos, videos, and interactive features like Stories and Reels, PTM Gunung Salak successfully engages audiences, strengthens emotional connections, and increases brand awareness. However, challenges include inconsistent posting, suboptimal content quality, and limited audience interaction. Therefore, optimizing digital content strategies and enhancing visual communication are essential to reinforce brand awareness in the digital era.